Interferon-λ Receptor Expression: Novel Reporter Mouse Reveals Within-and Cross-Tissue Heterogeneity - Linden, Julian; Schnepf, Daniel; Wischnewski, Marilena; Ye, Liang; Gawron, Jana; Ohnemus, Annette; Friedrich, Christin; Gasteiger, Georg; Staeheli, Peter (Journal of Interferon and Cytokine Research, 2020)
Interferon-λ (IFN-λ) plays an important role in mucosal immunity, but reliable information regarding the expression of the IFN-λ receptor in individual cells is still missing. One reason for this knowledge gap is the lack of antibodies that specifically recognize the unique IFNLR1 subunit of the dimeric IFN-λ receptor complex. In this study, we investigated whether a reporter mouse carrying a bacterial β-galactosidase gene inserted into the Ifnlr1 locus could be used to visualize IFN-λ receptor-expressing cells in whole organs. First we confirmed that insertion of the reporter cassette inactivated the Ifnlr1 gene, and that gene function could be restored by removing the β-galactosidase insert by site-specific recombination. When whole tissues were analyzed, prominent β-galactosidase activity was confined to the intestinal tract of reporter mice. However, only the snout expressed β-galactosidase at levels high enough for reliable detection in whole tissue extracts. Interestingly, individual epithelial cells in the upper airways expressed β-galactosidase activity to variable degrees as determined by flow cytometry and histology, suggesting a remarkable heterogeneity in IFNLR1 expression levels. Taken together, our results demonstrate a surprisingly strong within-and cross-tissue heterogeneity of IFNLR1 expression that may have physiological implications.
CRIS-Team Scopus Importer:2023-03-23
Keywords: epithelial cells; interferon-λ; mucosal immunity; reporter mouse